Seroprevalence of Visceral Leishmaniasis in Children Up To 12 Years Old of Rural Areas from Kermanshah Province, Western Part of Iran - Kaveh Sedaghatmanesh; Hooshang Khazan; Behnaz Akhoundi; Sasan Khazaei; Zahra Kakooei; Mehdi Mohebali (Iranian Journal of Parasitology, 2023)
Background: After the earthquake in 2017 a few new cases of visceral leishmaniasis (VL) were reported from SarPol-e-Zahab district of Kermanshah Province, western part of Iran. This study was conducted to determine the seroprevalence in Kermanshah Province.